Pengaruh Kualitas Pelayanan, Word of Mouth dan Kepercayaan terhadap Kepuasan Konsumen di Chic Beauty Salon and Studio - Asparini, Ni Wayan Diah; Ayu Wimba, I Gusti; Suasti Puja, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Currently, competition between beauty industry markets is increasingly competitive. This is evidenced by the emergence of more and more pharmacies. Chic Beauty Salon And Studio is one of the salons whose business activities are inseparable from the increasingly competitive market conditions. The purpose of this study was to determine the effect of service quality, word of mouth and trust on consumer satisfaction. This study was conducted at Apotekku By Pass in Tabanan and the population of this study were consumers of Chic Beauty Salon And Studio with a total of 3,358 consumers. Determination of the number of samples was carried out using the Slovin formula so that the number of samples was set at 97 people. The sampling technique used was purposive sampling. Data collection was carried out using a questionnaire. To test the hypothesis, multiple linear regression analysis, t-test and coefficient of determination were carried out. From the results of the analysis, it can be concluded that: 1) service quality has a positive and significant effect on consumer satisfaction, 2) word of mouth has a positive and significant effect on consumer satisfaction, 3) trust has a positive and significant effect on consumer satisfaction.